Neuromuscular monitoring and incidence of postoperative residual neuromuscular blockade: a prospective observational study - Alessandra Piersanti; Rossella Garra; Fabio Sbaraglia; Miryam Del Vicario; Rosa Lamacchia; Marco Rossi (Journal of Anesthesia, Analgesia and Critical Care)
Abstract Background Neuromuscular blocking agents (NMBAs) are routinely used in anesthesia practice. An undetected, incomplete recovery of neuromuscular function at the end of surgery potentially exposes patients to clinical deterioration in the postoperative period. The aim of this study was to investigate the incidence of postoperative residual neuromuscular blockade (RNMB) in a cohort of patients receiving NMBAs. Methods We enrolled 90 spontaneously breathing adult patients admitted to the recovery room (RR) after completion of surgeries having received at least 1 dose of NMBA. Anesthesia management, the dosage of NMBA used, and whether monitoring of neuromonitoring function was employed or if a reversal agent was administered were all at the discretion of the attending anesthesiologist, who was unaware that neuromuscular function was going to be monitored in the RR. The primary objective of this study was to determine the incidence of RNMB (defined as a train-of-four ratio ≤ 0.9). The secondary objectives were the number of postoperative adverse respiratory events and, for exploratory purposes, the estimation of potential risk factors through logistic regression analysis. Results RNMB occurred in 5 (5%) patients who had received only one dose of NMBA at induction of anesthesia. Two patients with RNMB (40%) required O2 supplementation during monitoring in the RR, compared to 11 patients in the rest of the sample (13%). Additionally, 2 of these patients (2%) required O2 supplementation before hospital discharge due to O2 desaturation < 92%. None of the patients with RNMB had received a reversal of neuromuscular blockade at the end of surgery. The association between RNMB and potential risk factors, assessed through multivariable logistic regression did not yield significant results for any of the considered variables. Conclusions RNMB can occur even when a single dose of NMBAs is administered. Despite decades of extensive literature on the risks of RNMB and recent guidelines, routine monitoring of neuromuscular function and pharmacologic reversal of NMBA is still substandard. Routine monitoring of neuromuscular function is strongly advocated to enhance the level of patient care. Trial registration The study was registered at ClinicalTrials.gov ( NCT06193213 , date of registration: 05/01/2024).